DNA damage in children with β-thalassemia minor: genotoxicity assessment by comet assay - Deniz Menderes; Esra Emerce; Tayfun Göktaş; Gonca Çakmak; Deniz Aslan (The Turkish Journal of Pediatrics)
Background. In transfusion-dependent forms of β-thalassemia, chronic anemia and iron overload lead to the development of oxidative stress-related DNA damage. In β-thalassemia minor (β-Tm), oxidative stress resulting from an unbalanced globin chain ratio has been documented, even in the absence of anemia and its complications. However, the status of oxidative stress-related DNA damage has not yet been elucidated. The aim of this study was to assess DNA damage in β-Tm in a pediatric population.